An Mentoring Listening Skills: YouTube Practical Psychology for Enhancing English Competence of Students at University - Sariakin, Sariakin; Yulsafli, Yulsafli; Muchsin, Muchsin; Usman, Musliadi B (Jurnal Ilmiah Peuradeun, 2023)
Listening is one of the language skills that students must master. However, it is difficult for students to master it. Some factors make it difficult for students to master it, and one of them is that the method or media used by lecturers in the teaching and learning process is not suitable or comfortable. This study aimed to determine if the English study program students of BBG University who are taught listening skills through watching YouTube Channel Practical Psychology are more successful than those who are taught listening skills without watching YouTube Channel Practical Psychology. This research employed quantitative methods and a pre-experiment design with a single group: pre-test - post-test. The population of this study was the entire third-semester English department students at BBG University, was 26 students divided into one class. The necessary data was obtained through testing, and the obtained data was analyzed using the N-Gain Score. N-Gain Score was calculated to be 0.41. It indicated a disparity between the students’ listening abilities before being taught via the YouTube Channel Applied Psychology. After they were taught by watching the YouTube Channel Practical Psychology, the difference was 41%. It means that the students’ listening competence increased by 41% after they were taught through watching YouTube Channel Practical Psychology.